Militarismens ontologi: Krig och fred som mänskliga existensvillkor i Frida Stéenhoffs Stridbar ungdom och Elin Wägners Släkten Jerneploogs framgång - Mårsell, Maria (Tidskrift för litteraturvetenskap, 2021)
The Ontology of Militarism: War and Peace as Conditions of Existence in Frida Stéenhoff ’s Stridbar ungdom and Elin Wägner’s Släkten Jerneploogs framgång This article claims that Western culture is tinged by an idea of an ontology of militarism. By analyzing how bodies are militarized because of this presumption, and how resistance against that very same presumption is carried out in Frida Stéenhoff ’s Stridbar ungdom (1906) and Elin Wägner’s Släkten Jerneploogs framgång (1916), this article presents an alternative understanding of the relationship between militarism and peace. Both works problematize and challenge the idea of militarism as a pre-condition for the human being. Finally, utopia, rather than militarism, emerges as indispensable to human beings.